Miscellany a Note on Modeling Tournaments - Koh, Winston T. H. (Institutional Knowledge at Singapore Management University, 1992)
Existing studies on tournaments utilize different specifications of the production function. Comparison of these results is difficult. This paper shows that the strategic behavior of agents in a tournament can be analyzed more generally using a specification of the production function along the lines of the standard agency model. I also show that in mixed contests, the more able contestant would in equilibrium have a higher probability of winning the contest despite attempts to use effort to compensate for ability by the less able contestant (Proposition 3).